(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2020)
There is no need to comment further on the difficult situation we are all facing due to the pandemic that is ravaging us; it is probably the greatest challenge humanity has faced since World War II. In view of the need to combat this serious public health problem, Federal Law No. 13,979/2020 was enacted, which "provides for measures to deal with the public health emergency of international importance resulting from the coronavirus responsible for the 2019 outbreak". Among the measures that the competent authorities can take are: a) determining social isolation and quarantine; b) exceptional restrictions on entry and exit from the country; c) requisitioning goods and services from natural and legal persons; d) temporary authorization to import products without registration with Anvisa. In the same vein, new rules were created for the acquisition by the Public Administration of goods and services to deal with the public health emergency. Of particular note here is Article 4 of Law No. 13,979/2020, which prescribes that bidding is waived for the purchase of products intended to combat the epidemic.